Capital formation in the Caribbean : a management approach - Serrano, Guido (OAS. Department of Economic Affairs Washington, DCUS, 1987)
Discusses capital formation through investment by business firms, state enterprises, and social investment by Government. Examines macro management of investment or aggregate package of investment activities which confirm to the national process of capital formation. Discusses the establishment of national goals for investment and way in which national investment can be run to achieve expected levels of growth through government leadership of a national investment process. Emphasizes the management approach to investment. Topics discussed include inter alia, investment motivation, project cycle, instruments for investment decisions, management of projects construction, and techniques for investment planning.